Selling Point Influincer di Sosial Media: Studi Kasus Analisis Resepsi Influincer Keanu Angelo di Kalangan Anak Muda - agustini, vilya dwi (Borobudur Communication Review, 2023)
In the past decade the shift of old media to new media has caused various phenomena. Among other things, the appearance of an influencer or celebrity. Personal branding ability is a necessity to captivate the hearts of the audience. "Where is Ahlak", "elang, elang, I say your father" and a line of familiar jargon brought up by an influencer. Some harsh words, a different appearance from most men and often shows the nightlife to be a "selling point" of a @Keanuagl. Stuart hall, as a reviewer of media texts in the encoding and decoding process, sees media audiences as active organs. There are different understandings and interpretations, Hall divides the media audience into three positions among others: dominant-hegemonic reading, negotiated reading, and oppositional-hegemonic reading..